1987
DOI: 10.1063/1.98744
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency Al0.3Ga0.7As solar cells grown by molecular beam epitaxy

Abstract: This letter reports the growth of high-efficiency Al0.3Ga0.7As solar cells by molecular beam epitaxy. As the growth temperature increases from 650 to 750 °C, the concentration of midgap electron traps in the active layers decreases from 4×1015 to less than 3×1013 cm−3 and the hole diffusion length in the layers improves from 2.0 to 2.6 μm. For cells grown at 750 °C, an efficiency of 14.6% (AM1.5, 100 mW/cm2 for an active area) is obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 11 publications
2
17
0
Order By: Relevance
“…The lower EQE at longer wavelengths, with a characteristic shoulder in the EQE curve close to the band-edge, is a well-known phenomenon for AlxGa1-xAs solar cells [8][9][10][11][12]. It has been demonstrated that this issue can be addressed by using Se instead of Si as the dopant for the n-type regions [15].…”
Section: Photovoltaic Propertiesmentioning
confidence: 95%
See 2 more Smart Citations
“…The lower EQE at longer wavelengths, with a characteristic shoulder in the EQE curve close to the band-edge, is a well-known phenomenon for AlxGa1-xAs solar cells [8][9][10][11][12]. It has been demonstrated that this issue can be addressed by using Se instead of Si as the dopant for the n-type regions [15].…”
Section: Photovoltaic Propertiesmentioning
confidence: 95%
“…Growth temperature has long been established as a key parameter in order to reduce oxygen contamination, and thus to enhance the material quality and performance of AlxGa1-xAs solar cells [6,[8][9]11], with the optimal temperature greatly dependent on the Al content x. In this contribution, we present and discuss recent progress in the MBE growth of 1.70-eV Al0.22Ga0.78As solar cells on GaAs substrates.…”
Section: Alxga1-xas Photovoltaic Solar Cells Have Recently Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…These are listed in Table I. We also calculated the EREs of III-V/Si and III-V solar cells in [15][16][17] using this approach. The results are listed in Table II.…”
Section: External Radiative Efficiencies Of State-of-the Art Iii/v Onmentioning
confidence: 99%
“…13 The poor performance of the conventional tunnel junction demonstrates the difficulty of making high quality tunnel junctions using conventional designs. The main limitation is the use of AlGaAs for the wider-band-gap cell; it is difficult to generate large photocurrent densities in an Al-GaAs cell due to defects which allow exciton recombination.…”
Section: Increased Efficiency In Multijunction Solar Cells Through Thmentioning
confidence: 99%